2020
DOI: 10.3390/molecules25051079
|View full text |Cite
|
Sign up to set email alerts
|

Novel 2,4-Disubstituted-1,3-Thiazole Derivatives: Synthesis, Anti-Candida Activity Evaluation and Interaction with Bovine Serum Albumine

Abstract: Herein we report the synthesis of two novel series of 1,3-thiazole derivatives having a lipophilic C4-substituent on account of the increasing need for novel and versatile antifungal drugs for the treatment of resistant Candida sp.-based infections. Following their structural characterization, the anti-Candida activity was evaluated in vitro while using the broth microdilution method. Three compounds exhibited lower Minimum Inhibitory Concentration (MIC) values when compared to fluconazole, being used as the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The structure-activity relationship studies indicated that the modifications in the aryl ring play an important role for enhancing the activity. The combination of bromo Pricopie et al [72] taking into account the increasing need for novel antifungal drugs for resistant Candida sp. Infection, and based on the results of their previous work [65], synthesized two novel series of 1,3-thiazole derivatives (51a-d, 52a, Figure 18) with lipophilic C4 substituent and evaluated their antifungal activity against three human pathogenic Candida species (Figure 17).…”
Section: Thiazole Derivatives As Antimicrobial Agentsmentioning
confidence: 99%
“…The structure-activity relationship studies indicated that the modifications in the aryl ring play an important role for enhancing the activity. The combination of bromo Pricopie et al [72] taking into account the increasing need for novel antifungal drugs for resistant Candida sp. Infection, and based on the results of their previous work [65], synthesized two novel series of 1,3-thiazole derivatives (51a-d, 52a, Figure 18) with lipophilic C4 substituent and evaluated their antifungal activity against three human pathogenic Candida species (Figure 17).…”
Section: Thiazole Derivatives As Antimicrobial Agentsmentioning
confidence: 99%
“…The results obtained by molecular docking show the importance of the s mentioned in the in vitro results section and suggest that the mechanism of a compounds is by allosteric inhibition, since there is no interaction of the mole the active site of the molecule. This could be associated with a reduction in the the molecules 5a and 5f since the mechanism of action is not related to the cov dination of the heme group of lanosterol-14α-demethylase, as is the case for fungal azoles [41]. These data is supported by cytotoxic tests carried out in th section (Section 3.3).…”
Section: Molecular Dockingmentioning
confidence: 63%
“…Ghuman et al, when analyzing the drug-binding specificity of HSA, described very well the seven identified binding sites named as FA1 through FA7 where fatty acids bind to albumin [ 35 ]. Even before determining the crystallographic structure of HSA, Sudlow’s sites were proposed [ 36 , 37 , 38 ]. Sudlow’s drug site 1, DS1, is formed by an extension and widening of site FA7 towards the site FA2 and can consequently accommodate ligands bulkier than fatty acids.…”
Section: Resultsmentioning
confidence: 99%